2017
DOI: 10.1002/2016ja023267
|View full text |Cite
|
Sign up to set email alerts
|

Rapid precipitation of radiation belt electrons induced by EMIC rising tone emissions localized in longitude inside and outside the plasmapause

Abstract: By performing test particle simulations of relativistic electrons scattered by electromagnetic ion cyclotron (EMIC) rising tone emissions, we find a nonlinear scattering process named SLPA (Scattering at Low Pitch Angle) totally different from the nonlinear wave trapping. The nonlinear wave trapping, occurring for high pitch angles away from the loss cone, scatters some of resonant electrons to lower pitch angles, and a fraction of the electrons is further transported into the loss cone by SLPA after being rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(130 citation statements)
references
References 25 publications
(81 reference statements)
6
124
0
Order By: Relevance
“…In addition, Kubota and Omura (2017) have suggested that the precipitation of relativistic electrons is caused through two processes: the nonlinear wave trapping at large pitch angles and SLPA (scattering at low pitch angle) at small pitch angles. SLPA causes a strong scattering and precipitation for small pitch angle electrons without nonlinear wave trapping.…”
Section: 1029/2019ja026772mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Kubota and Omura (2017) have suggested that the precipitation of relativistic electrons is caused through two processes: the nonlinear wave trapping at large pitch angles and SLPA (scattering at low pitch angle) at small pitch angles. SLPA causes a strong scattering and precipitation for small pitch angle electrons without nonlinear wave trapping.…”
Section: 1029/2019ja026772mentioning
confidence: 99%
“…SLPA causes a strong scattering and precipitation for small pitch angle electrons without nonlinear wave trapping. Based on the discussion in Kubota and Omura (2017), SLPA condition of a pitch angle α is Combined with the SLPA effect at low pitch angles, the relativistic electrons precipitate in several seconds.…”
Section: 1029/2019ja026772mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonlinear interaction of relativistic electrons with a model EMIC wave packet, corresponding to the emission with rising frequency, has been studied through theoretical analysis and test particle simulations in Grach and Demekhov (, ), Kubota and Omura (), and Omura & Zhao (, ). Kubota and Omura () showed that combined scattering process of the nonlinear wave trapping and another nonlinear regime “SLPA” (scattering at low pitch angle) can lead to the rapid loss of relativistic electrons. The authors explained “SLPA” regime by the Lorentz force term in the equation for the particle phase (hereafter termed force bunching).…”
Section: Introductionmentioning
confidence: 99%
“…Exotic, but real process is the electron precipitation due to parasitic resonance with electromagnetic ioncyclotron (EMIC) waves [Summers, Thorne, 2003;Lazutin et al, 2011;Kubota, Omura, 2017]. EMIC waves are generated by ring current protons during the storm main phase.…”
Section: Interaction Of Electrons With High-frequency Wavesmentioning
confidence: 99%